2018
DOI: 10.4236/jbm.2018.67005
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Dyslipidemia as Indicators of Pathogenesis of Preeclampsia in Pregnant Sudanese Women

Abstract: Background: Preeclampsia (PE) still ranks as one of obstetrics major problems and is still a serious threat, mainly in underdeveloped countries where its incidence and mortality rates are higher and is a major cause of preterm birth and intra-uterine growth restriction. Aim: To evaluate the role of oxidative stress and dyslipidemia as indicators of pathogenesis and risks of preeclampsia in pregnant Sudanese women attending Wad-Medani Obstetrics and Gynecology Teaching Hospital. Material and Method: This was a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 50 publications
1
3
0
Order By: Relevance
“…Hyperlipidaemia in normal pregnancy is non-atherogenic, and attributed to hormonal changes. However, in preeclampsia, there is dysregulation of lipid metabolism, which manifests as abnormal maternal serum lipid levels [32][33][34]. Consistent with this study, several other studies have reported dyslipidaemia in preeclampsia and stated that abnormal lipid levels in pregnancy signi cantly contribute to the development of preeclampsia through the excessive deposition of triglycerides in the uterine spiral arteries which may result in endothelial dysfunction through the production of small dense LDL [32][33][34][35][36].…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Hyperlipidaemia in normal pregnancy is non-atherogenic, and attributed to hormonal changes. However, in preeclampsia, there is dysregulation of lipid metabolism, which manifests as abnormal maternal serum lipid levels [32][33][34]. Consistent with this study, several other studies have reported dyslipidaemia in preeclampsia and stated that abnormal lipid levels in pregnancy signi cantly contribute to the development of preeclampsia through the excessive deposition of triglycerides in the uterine spiral arteries which may result in endothelial dysfunction through the production of small dense LDL [32][33][34][35][36].…”
Section: Discussionsupporting
confidence: 76%
“…A healthy pregnancy is associated with physiologic hyperlipidemia to satisfy the demands of the developing foetus [32,33]. Hyperlipidaemia in normal pregnancy is non-atherogenic, and attributed to hormonal changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A healthy pregnancy is associated with physiologic hyperlipidemia to satisfy the demands of the developing fetus [ 34 , 35 ]. Hyperlipidemia in normal pregnancy is non-atherogenic, and attributed to hormonal changes.…”
Section: Discussionmentioning
confidence: 99%